Oral health status and self-perceived oral health satisfaction among residents in the largest care home in east coast Malaysia and its associated factors: a cross-sectional study - Mohd, Farah Natashah; Said, Abdul Hadi; Yusof, Muhammad Zubir; Ismail, Nor Iziana; Musa, Nor Mulyani (Wolters Kluwer - Medknow, 2020)
Aim: To Assess the oral health status among residents living in care home and to determine its association with their self-perceived oral health satisfaction. Materials and Methods: A cross-sectional study was conducted from July to August 2018 among 75 residents of Rumah Ehsan, Terengganu (the largest care home in east coast Malaysia). The oral health status of the residents was examined by one dental specialist based on two domains: the number of decayed, missing, and filled teeth (DMF-T) and the edentulous state. Their sociodemographic profile and self-perceived oral health status were collected through interviews. Multiple logistic regressions were used to determine factors associated with oral health satisfaction. Results: Unsurprisingly, majority of residents had high DMF-T score with median DMF-T score of 29.0 (interquartile range [IQR] = 12). On the contrary, majority of them (64%) perceived that they had good oral health status and 68% were satisfied with their current oral health status. There was no significant association between the actual oral health status and their perceived satisfaction. However, older age, Malay, and those eating dependently were less likely satisfied with their oral health status. Meanwhile, those who were dependent to the staff to brush their teeth were more likely satisfied with their oral health status. Conclusion: There was a discrepancy between actual and self-perceived oral health status among residents in care home. Hence, every effort is necessary to improve the awareness and knowledge among them in order to improve the oral health.